A note on palindromic δ-vectors for certain rational polytopes - Fiset, Matthew; Kasprzyk, Alexander M. (2008)
Let P be a convex polytope containing the origin, whose dual is a lattice polytope. Hibi's Palindromic Theorem tells us that if P is also a lattice polytope then the Ehrhart δ-vector of P is palindromic. Perhaps less well-known is that a similar result holds when P is rational. We present an elementary lattice-point proof of this fact.